Purification and characterization of membrane-bound peroxidases from Metroxylon sagu - Onsa, Galila Hassan; Saari, Nazamid; Selamat, Jinap; Bakar, Jamilah (Elsevier, 2004)
Two membrane-bound peroxidases, mPOD-I and mPOD-II, have been isolated and purified from Metroxylon sagu, using a combination of temperature-induced phase partitioning, DEAE-Toyopearl 650M, CM-Toyopearl 650 M and gel filtration. The mPOD-I and mPOD-II had molecular mass of 51.2 and 43.8 kDa, respectively, as determined by SDS–PAGE. Both enzymes showed high efficiency of interaction with the substrates. The isoenzymes were highly inhibited by ascorbic acid, metabisulfite, l-cysteine and p-coumaric acid. The inhibition mode of action and inhibition rate constant (Ki) values for these inhibitors were determined. Their activities were highly enhanced by Al3+, Ca2+ and Fe3+ but they were moderately inhibited by Zn2+.